La fixation de l'azote par les legumineuses fourrageres en Afrique subsaharienne: Potentialites et contraintes - Haque, I.; Jutzi, S.C. (1984)
Reviews the present state of knowledge about the biological contribution of nitrogen by forage legumes in sub-Saharan Africa; indicates the main factors limiting the contribution of biological N by forage legumes; highlights the potentials of legume - food crop - livestock interactions in various production systems; suggests areas where intensified research is justified in terms of scientific knowledge and practical benefits.